An efficient synthesis of the guaiane sesquiterpene (−)-isoguaiene by domino metathesis - Wang, Yuzhou; Darweesh, Ahmed F.; Zimdars, Patrick; Metz, Peter (Beilstein Journal of Organic Chemistry, 2019)
(−)-Isoguaiene was prepared from (S)-citronellal in only 9–10 steps with good overall yields. Either a trienyne or a dienediyne metathesis and highly diastereoselective organocatalytic Michael additions of aldehydes derived from (S)-citronellal served as the key transformations.
Keywords: domino reactions; metathesis; Michael addition; organocatalysis; terpenes

(untitled) - Cullmann, F.; Becker, H. (Phytochemistry, 1998)

(untitled) - Saritas, Y.; Bülow, N.; Fricke, C.; König, W. A.; Muhle, H. (Phytochemistry, 1998)

(untitled) - Tabanca, N.; Bedir, E.; Ferreira, D.; Slade, D.; Wedge, D. E.; Jacob, M. R.; Khan, S. I.; Kirimer, N.; Baser, K. H. C.; Khan, I. A. (Chem. Biodiversity, 2005)

(untitled) - Baser, K. H. C.; Tabanca, N.; Kirimer, N.; Bedir, E.; Khan, I. A.; Wedge, D. E. (Pure Appl. Chem., 2007)

(untitled) - Bohlmann, F.; Zdero, C.; Lonitz, M. (Phytochemistry, 1977)

(untitled) - Blay, G.; Garcia, B.; Molina, E.; Pedro, J. R. (Org. Lett., 2005)

(untitled) - Knüppel, S.; Rogachev, V. O.; Metz, P. (Eur. J. Org. Chem., 2010)

(untitled) - Barthel, A.; Kaden, F.; Jäger, A.; Metz, P. (Org. Lett., 2016)

(untitled) - Hoye, T. R.; Jeffrey, C. S.; Tennakoon, M. A.; Wang, J.; Zhao, H. (J. Am. Chem. Soc., 2004)

(untitled) - Chi, Y.; Gellman, S. H. (Org. Lett., 2005)

(untitled) - Banti, D.; North, M. (Tetrahedron Lett., 2003)

(untitled) - Spiegel, D. A.; Schroeder, F. C.; Duvall, J. R.; Schreiber, S. L. (J. Am. Chem. Soc., 2006)

(untitled) - Yuan, W.; Wei, Y.; Shi, M. (ChemistryOpen, 2013)

(untitled) - Zuercher, W. J.; Scholl, M.; Grubbs, R. H. (J. Org. Chem., 1998)

(untitled) - Zahel, M.; Wang, Y.; Jäger, A.; Metz, P. (Eur. J. Org. Chem., 2016)

(untitled) - Hamada, N.; Kazahaya, K.; Shimizu, H.; Sato, T. (Synlett, 2004)

(untitled) - Tietze, L. F.; Denzer, H.; Holdgrün, X.; Neumann, M. (Angew. Chem., 1987)
Angew. Chem., Int. Ed. 1987, 26, 1295-1297. doi:10.1002/anie.198712951

(untitled) - Naruse, Y.; Yamamoto, H. (Tetrahedron, 1988)

(untitled) - Griffith, W. P.; Ley, S. V.; Whitcombe, G. P.; White, A. D. (J. Chem. Soc., Chem. Commun., 1987)

(untitled) - Yarovaya, O. I.; Salomatina, O. V.; Korchagina, D. V.; Polovinka, M. P.; Barkhash, V. A. (Russ. J. Org. Chem., 2002)

(untitled) - Sutherland, A. J.; Sutherland, J. K.; Crowley, P. J. (J. Chem. Soc., Perkin Trans. 1, 1996)

(untitled) - Michel, P.; Gennet, D.; Rassat, A. (Tetrahedron Lett., 1999)

(untitled) - Corey, E. J.; Fuchs, P. L. (Tetrahedron Lett., 1972)

(untitled) - Radtke, L.; Willot, M.; Sun, H.; Ziegler, S.; Sauerland, S.; Strohmann, C.; Fröhlich, R.; Habenberger, P.; Waldmann, H.; Christmann, M. (Angew. Chem., 2011)
Angew. Chem., Int. Ed. 2011, 50, 3998–4002. doi:10.1002/anie.201007790

(untitled) - Gao, P.; Xu, P.-F.; Zhai, H. (J. Org. Chem., 2009)

(untitled) - Abidi, S. L. (Tetrahedron Lett., 1986)

(untitled) - Garber, S. B.; Kingsbury, J. S.; Gray, B. L.; Hoveyda, A. H. (J. Am. Chem. Soc., 2000)

(untitled) - Gessler, S.; Randl, S.; Blechert, S. (Tetrahedron Lett., 2000)

(untitled) - Osborn, J. A.; Jardine, F. H.; Young, J. F.; Wilkinson, G. (J. Chem. Soc. A, 1966)